2010
DOI: 10.1101/gad.1964410
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RIP2's tyrosine kinase activity limits NOD2-driven cytokine responses

Abstract: Upon intracellular bacterial exposure, the Crohn's disease and sarcoidosis susceptibility protein NOD2 (nucleotide oligomerization domain protein 2) binds to the protein kinase RIP2 (receptor-interacting protein 2) to coordinate NF-kB (nuclear factor k B)-mediated cytokine responses. While RIP2 clearly has kinase activity, the function of its kinase domain has been enigmatic. Although originally classified as a serine-threonine kinase based on homology scans, we find that RIP2 also has tyrosine kinase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
201
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 183 publications
(210 citation statements)
references
References 50 publications
7
201
1
1
Order By: Relevance
“…WEHI-345 inhibits RIPK2 activity in vitro with an IC 50 of 134 nM, while IC 50 against other RIP Kinases is greater than 10 mM. Treatment with WEHI-345 significantly inhibited IL-6 secretion from Raw 267.4 cells at 50 nM, showing a 10-fold stronger inhibition than erlotinib and gefitinib in an identical assay 22 . In cells, WEHI-345 blocked NOD-dependent cytokine production but spared necroptosis ARTICLE signalling mediated by RIPK1 and RIPK3.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…WEHI-345 inhibits RIPK2 activity in vitro with an IC 50 of 134 nM, while IC 50 against other RIP Kinases is greater than 10 mM. Treatment with WEHI-345 significantly inhibited IL-6 secretion from Raw 267.4 cells at 50 nM, showing a 10-fold stronger inhibition than erlotinib and gefitinib in an identical assay 22 . In cells, WEHI-345 blocked NOD-dependent cytokine production but spared necroptosis ARTICLE signalling mediated by RIPK1 and RIPK3.…”
Section: Discussionmentioning
confidence: 85%
“…Upon activation, RIPK2 autophosphorylates on Ser176 and on Tyr474 (refs 22,25). While Ser176 phosphorylation is essential for RIPK2 activity, phosphorylation of Tyr474 enhances, but is not essential for signalling 22 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The CARDcontaining kinase RIP2 is required for NF-κB activation. The function of RIP2 tyrosine kinase activity is unclear, although it was recently shown that kinase inhibitors could prevent MDP-induced cytokine responses [79]. Although RIP2 binds to NEMO, it is not thought that RIP2 tyrosine kinase activity mediates IKK phosphorylation directly.…”
Section: Pattern Recognition Receptorsmentioning
confidence: 99%